Drawing Guideline for ‘Hip and Pelvis’: Plot with Error Bar - Kim, Jeehyoung (Hip Pelvis, 2020)
The appropriate plots effectively convey the author's conclusions to the readers. ‘Hip and Pelvis’ will provide a series of special articles to show how to make consistent and excellent plots easier. In this article, we will cover plots with error bars.